Value of 18-F-FDG PET/CT and CT in the Diagnosis of Indeterminate Adrenal Masses. (2nd February 2015) - Launay, Nathalie; Silvera, Stéphane; Tenenbaum, Florence; Groussin, Lionel; Tissier, Frédérique; Audureau, Etienne; Vignaux, Olivier; Dousset, Bertrand; Bertagna, Xavier; Legmann, Paul
Abstract : The purpose of this paper was to study the value of 18-FDG PET/CT and reassess the value of CT for the characterization of indeterminate adrenal masses. 66 patients with 67 indeterminate adrenal masses were included in our study. CT/MRI images and 18F-FDG PET/CT data were evaluated blindly for tumor morphology, enhancement features, apparent diffusion coefficient values, maximum standardized uptake values, and adrenal-to-liver maxSUV ratio. The study population comprised pathologically confirmed 16 adenomas, 19 metastases, and 32 adrenocortical carcinomas. Macroscopic fat was observed in 62.5% of the atypical adenomas at CT but not in malignant masses. On 18F-FDG PET/CT, SUVmax and adrenal-to-liver maxSUV ratio were significantly lower in adenomas than in malignant tumors. An SUVmax value of less than 3.7 or an adrenal-to-liver maxSUV ratio of less than 1.29 is highly predictive of benignity.